1993
DOI: 10.1038/hdy.1993.149
|View full text |Cite
|
Sign up to set email alerts
|

Generating high variability of B chromosomes in Eyprepocnemis plorans (grasshopper)

Abstract: /n and tDepartamento de Genét/ca, Facultad de B/o/ogIa, Un/vers/dad Comp/utense de Madrid, E-28040 Madrid, Spa/n Twenty-eight progeny analyses (PAs) performed on specimens of E. plorans collected from four natural Iberian populations have been informative about the transmission of rare B chromosome types or the de novo origin of some of them. At least ii rare B-types have been found in addition to the predominant ones: B1 in Daimuz, B2 in Jete and Salobreña, and B5 in Fuengirola. The presence in two controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…The largest Bs showed some of the features and behaviour typical of isochromosomes: they are very large and metacentric, with largely symmetrical C-bands in both arms; they often display a folded configuration and in metaphase I they often form univalent rings. Large Bs are present in a few species, among animals they are reported mainly in the Orthoptera (Jones and Rees, 1982), and have been observed more recently in a number of fishes (reviewed in Ziegler et al, 2003).The peculiar features and meiotic behaviour of iso-B chromosomes have been studied in plants (Jones et al, 1989;Santos et al, 1995), in Orthoptera (Hewitt, 1979;Fletcher and Hewitt, 1988;Henriques-Gill et al, 1984;Ló pez-Leó n et al, 1993) and in fishes (Mestriner et al, 2000). Iso-B chromosomes are generated by centromere misdivision and nondisjunction and they can derive from the rearrangement of B chromosomes, as reported in the grasshopper Eyprepocnemis plorans (Ló pez-Leó n et al, 1993) or from an A chromosome as reported in the fish Astyanax scabripinnis (Mestriner et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The largest Bs showed some of the features and behaviour typical of isochromosomes: they are very large and metacentric, with largely symmetrical C-bands in both arms; they often display a folded configuration and in metaphase I they often form univalent rings. Large Bs are present in a few species, among animals they are reported mainly in the Orthoptera (Jones and Rees, 1982), and have been observed more recently in a number of fishes (reviewed in Ziegler et al, 2003).The peculiar features and meiotic behaviour of iso-B chromosomes have been studied in plants (Jones et al, 1989;Santos et al, 1995), in Orthoptera (Hewitt, 1979;Fletcher and Hewitt, 1988;Henriques-Gill et al, 1984;Ló pez-Leó n et al, 1993) and in fishes (Mestriner et al, 2000). Iso-B chromosomes are generated by centromere misdivision and nondisjunction and they can derive from the rearrangement of B chromosomes, as reported in the grasshopper Eyprepocnemis plorans (Ló pez-Leó n et al, 1993) or from an A chromosome as reported in the fish Astyanax scabripinnis (Mestriner et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of morphology and C banding pattern, more than 50 B variants have been described in natural populations of E. plorans (Henriques-Gil et al, 1984;Ló pez-Leó n et al, 1993). The B 1 chromosome was considered the original B in Spanish populations (Henriques-Gil et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The autosomes may be classified into three size groups: Long (L 1 -L 2 ), Medium (M 3 -M 8 ) and Small (S 9 -S 11 ), the X chromosome size being intermediate between those of L 2 and M 3 . Previous studies have shown that almost all E. plorans populations analysed from the Mediterranean region and the Caucasus show the polymorphism for B chromosomes (Camacho et al, 1980;Henriques-Gil et al, 1984;López-Fernández et al, 1992;Ló pez-Leó n et al, 1993;Cabrero et al, 1997;Bugrov et al, 1999). This polymorphism has revealed the existence of an arms race between A and B chromosomes leading the system through successive stages with B chromosomes passing from parasitic to near-neutral and vice versa, thus facilitating B-polymorphism regeneration (Zurita et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species has a widespread polymorphism for B chromosomes that includes more than 40 different variants (Camacho et al, 1980;Henriques-Gil et al, 1984;Henriques-Gil and Arana, 1990;Lopez-Leon et al, 1993). The individuals analyzed in this study carried B5, the most common variant in the central area of the species distribu-tion in Spain, and B1, believed to be the most primitive variant.…”
mentioning
confidence: 99%